Painting today - Godfrey, Tony. (London : New York ; Phaidon, 2009)
A worldwide survey of painting from the 1970's to the present.
Includes bibliographical references and index.
Keywords: Painting, Modern -- 20th century; Painting, Modern -- 21st century; Schilderkunst